2017
DOI: 10.22159/ajpcr.2017.v10i12.21963
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Novel Antibacterial and Anti-Inflammatory Cream Containing Muntingia Calabura Leaves Extract

Abstract: Objective: The main objective of the present study was to formulate antibacterial and anti-inflammatory cream using Muntingia calabura leaves extract.Methods: 500 g of matured leaves of M. calabura were extracted with 70% methanol using maceration method for a week. The antibacterial activity of the extract and formulated cream in different concentration was investigated against two Gram-positive bacteria (Staphylococcus aureus and Bacillus cereus) and two Gram-negative bacteria (Escherichia coli and Pseudomon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…The result obtained was in line with previous findings where the ethanolic extract of C.odorata leaves reveals the presence of medicinally valued bioactive components like saponins, tannins, terpenoid, and flavonoids [28]. Besides, other studies also showed that ethanolic extract was rich in secondary metabolites such as alkaloids, flavonoids, tannins, saponins, terpenoids, glycosides, cardiac glycosides, and phenols [24,25].…”
Section: Qualitative Phytochemical Screeningsupporting
confidence: 90%
See 1 more Smart Citation
“…The result obtained was in line with previous findings where the ethanolic extract of C.odorata leaves reveals the presence of medicinally valued bioactive components like saponins, tannins, terpenoid, and flavonoids [28]. Besides, other studies also showed that ethanolic extract was rich in secondary metabolites such as alkaloids, flavonoids, tannins, saponins, terpenoids, glycosides, cardiac glycosides, and phenols [24,25].…”
Section: Qualitative Phytochemical Screeningsupporting
confidence: 90%
“…The extracts were then filtered using a vacuum pump. Then, the collective extracts were concentrated using a rotary evaporator at 34 °C before weighted and stored in refrigerators at a temperature of 4 °C [16,17].…”
Section: Maceration Extractionmentioning
confidence: 99%
“…After heating, the aqueous phase (Part B) was added in portions to the oil phase (Part A) with continuous stirring until cooling of emulsifier occurred [ 22 ]. The creation of the galangal extract cream was done according to the method mentionedin reference [ 22 ]. A 5% w / w cream was prepared using the formula given below ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…the aqueous phase was prepared by dissolving the required amount of hexane extract in propylene glycol solvent and then adding it to water. The preservatives (methylparaben, triethanolamine) and the other water-soluble component glycerin, which was used as humectant, were dissolved in the aqueous phase and heated to 75 • C. After heating, the aqueous phase (Part B) was added in portions to the oil phase (Part A) with continuous stirring until cooling of emulsifier occurred [22]. The creation of the galangal extract cream was done according to the method mentionedin reference [22].…”
Section: Preparation Of the Herbal Antifungal Cream From Hexane Extractmentioning
confidence: 99%
“…The major compounds in PY plant are flavonoids, glycosides, glycoglycerolipids, cerebrosides, and monoacylmonogalatosylglycerol (Alam et al, 2016). Pure compounds and various types of PY extracts revealed several pharmacological properties, such as antiviral (Haetrakul et al, 2018), anti-diabetic (Abdullah, & Kasim, 2017), anti-inflammatory (Kuo et al, 2021;Wanikiat et al, 2008), antioxidant (Alam et al, 2017;Arullappan et al, 2014), and antimicrobial activities against Bacillus cereus, Escherichia coli (Arullappan et al, 2014;Sekar & Rashid, 2016), Salmonella enterica Typhimurium, Candida albicans (Arullappan et al, 2014), Staphylococcus aureus, and Pseudomonas aeruginosa (Sekar, & Rashid, 2016). PY extracts and their pure isolated compounds were also reported to induce wound closure by human gingival fibroblasts (Roeslan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%